2013
DOI: 10.1111/jog.12127
|View full text |Cite
|
Sign up to set email alerts
|

Differences in collagen ultrastructure of human first trimester decidua basalis and parietalis: Implications for trophoblastic invasion of the placental bed

Abstract: There are differences in the ultrastructure of collagen fibrils between basalis and parietalis, with thicker and disrupted fibrils within abundant amorphous tissue in basalis, and thinner uniform fibrils in parietalis. These differences may reflect an adaptive response by decidua or a direct consequence of the invading trophoblast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…It is known that this process requires trophoblast pass through ECM and remodeling of ECM. Collagen as an important component of ECM, which is highly expressed at the maternal-fetal interface, must undergo remodeling during trophoblast invasion [89]. Based on the current research, we speculate that, as shown in Figure 1, integrin expressed by trophoblast combines with collagen expressed at the maternal fetal interface to promote trophoblast adhesion.…”
Section: Trophoblast Invasionmentioning
confidence: 66%
“…It is known that this process requires trophoblast pass through ECM and remodeling of ECM. Collagen as an important component of ECM, which is highly expressed at the maternal-fetal interface, must undergo remodeling during trophoblast invasion [89]. Based on the current research, we speculate that, as shown in Figure 1, integrin expressed by trophoblast combines with collagen expressed at the maternal fetal interface to promote trophoblast adhesion.…”
Section: Trophoblast Invasionmentioning
confidence: 66%
“…As a collagenase, MMP-1 is responsible for the degradation of collagen-rich extracellular matrices, such as those abundantly found in the decidua and the myometrium. 45 MMP-1 was reported to be the highest downregulated MMP in PE cases. Specifically, there is a clear reduction in the MMP-1 + EVT population, suggesting its involvement in the reduced invasiveness observed in the pathophysiology of PE.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, fibrinoid is in direct contact with the trophoblast, and fibrin deposits are frequent in contact areas. The collagen fibres in the chorionic villi have a compact structure formed by fibrillar bundles between the vascular wall and the extravascular stroma (Castellucci, Kaufmann, & Bischof, ; Sinai Talaulikar, Kronenberger, Bax, Moss, & Manyonda, ). In the macaque monkey, synthesis and deposition of laminin, fibronectin and type IV collagen occur in basement membranes of distal columnar cells with increasing quantity (Blankenship, Enders, & King, ; Blankenship & King, ; King & Blankenship, ).…”
Section: Haemochorial Placentamentioning
confidence: 99%